Ethnic Foods and Food based Traditional Knowledge of Fishing community in Kerala, India - Ashok, Arathy; Sreejith, S.; Benjamin, Diana; Bindu, J.; Gopal, Nikita (Fishery Technology, 2021)
Ethnic food systems represent the culture, traditions and customs a community followsand can be considered to be on par with the ethno botanical food and medicinal knowledge. Fishing communities also possesses knowledge on the nutritional and medicinal values related to the diverse resources of the sea. Proper documentation of such systems can refurbish our food habits and can act as repositories for ensuring that these are back in the culinary practices. .This communication presents some of the information that was documented from a study carried out in six coastal districts of Kerala during 2015-2016 in 47 fishing villages focussed on the various indigenous traditional knowledge practised in fishing and highlights the various traditional fish based foods in the community. Distinct beliefs regarding nutritional and medicinal use of different fishes along different places in Kerala have also been discussed in this paper.